2016
DOI: 10.5194/amt-9-3325-2016
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of IASI-A and AATSR measurements of top-of-atmosphere radiance over an extended period

Abstract: Abstract. This study examines the trustworthiness

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The temporal stability of AATSR and its good radiometric calibration, especially for the 10.8 µm channel, have been verified against the high spectral resolution interferometer IASI on MetOp-A, which is the reference used by GSICS [20,21]. Similarly, ATSR-2's good radiometric calibration consistency to the level of 0.1 K has been verified by comparing with the high spectral resolution spectrometer AIRS [21].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The temporal stability of AATSR and its good radiometric calibration, especially for the 10.8 µm channel, have been verified against the high spectral resolution interferometer IASI on MetOp-A, which is the reference used by GSICS [20,21]. Similarly, ATSR-2's good radiometric calibration consistency to the level of 0.1 K has been verified by comparing with the high spectral resolution spectrometer AIRS [21].…”
Section: Introductionmentioning
confidence: 73%
“…The pre-launch calibration of the ATSRs demonstrated that the radiometric noise was below 0.05 K (at a reference of 270 K) in all thermal IR channels and was stable throughout the lifetimes of ATSR-2 and AATSR, and although variable for ATSR-1, the total drift of the mission was only 0.1 K [19]. The temporal stability of AATSR and its good radiometric calibration, especially for the 10.8 µm channel, have been verified against the high spectral resolution interferometer IASI on MetOp-A, which is the reference used by GSICS [20,21]. Similarly, ATSR-2's good radiometric calibration consistency to the level of 0.1 K has been verified by comparing with the high spectral resolution spectrometer AIRS [21].…”
Section: Introductionmentioning
confidence: 81%